Farm-based measures for reducing human and environmental health risks from chemical constituents in wastewater - Simmons, Robert W.; Qadir, Manzoor; Drechsel, Pay (2010)
There is a significant imbalance between the number of publications describing potential and actual environmental and health impacts from chemically contaminated wastewater, and reports outlining concrete options to minimize the related risks where conventional wastewater treatment is not available. This gap applies more to inorganic and organic contaminants than excess salts or nutrients. This chapter outlines some of the options available that could be considered in and around the farm, looking at heavy metals, salts, excess nutrients and organic contaminants. The emphasis is placed on low-cost options applicable in developing countries. While such measures can reduce negative impacts to a certain extent, it remains crucial to ensure that hazardous chemicals are replaced in production processes; industrial wastewater is treated at source and/or separated from other wastewater streams used for irrigation purposes; and fertilizer application rates and related possible subsidies adjusted to avoid over- fertilization.